International Activities of Young Technology Companies Located in Science and Technology Parks - Sobol, Dorota (Olsztyn Economic Journal, 2018)
This article presents selected results of the research carried out in the second half of 2017 as part of a research project entitled International business operations of companies located in science and technology parks in the Warmińsko-Mazurskie voivodeship. The aim of the study was to recognize the current and planned path of foreign expansion as well as to identify the main factors determining the internationalization of operations. To achieve the goal, literature studies on the subject and the conditions of internationalization of enterprises in relation to the SME group were carried out. Empirical studies were then conducted with the participation of three young, innovative enterprises located in science and technology parks in the Warmińsko-Masurskie Voivodeship. Due to the specificity of business operations and the desire to fully understand the paths of foreign expansion, the empirical study was carried out in two stages: an interview with the questionnaire method using a questionnaire survey and personal interviews with representatives of top management of individual companies to enrich the results obtained earlier (case study). The results presented are for demonstration only and may not be used for generalisation. Nevertheless, they are an inspiration to undertake in-depth studies of this subject.